FRI0331 Apremilast for the treatment of behçet's syndrome: a phase ii randomized, placebo-controlled, double-blind study. (23rd January 2014) - Hatemi, G.; Melikoglu, M.; Tunc, R.; Korkmaz, C.; Ozturk, B. T.; Mat, C.; Merkel, P. A.; Calamia, K. T.; Liu, Z.; Pineda, L.; Stevens, R. M.; Yazici, H.; et al.
Abstract : Background: Mucocutaneous manifestations of Behçet's syndrome (BS) can be resistant to conventional treatment and at times disabling. Apremilast (APR), an oral phosphodiesterase 4 inhibitor, modulates inflammatory pathways. Objectives: To investigate the efficacy of APR in BS patients with active oral ulcers (OU). Methods: Patients with BS without major organ involvement but ≥2 OU were randomized to APR 30 mg BID or PBO for 12 wks followed by a 12-wk active-treatment period for all patients and a 28-day post-tx observational follow-up. Primary endpoint was number of OU at wk 12. Secondary endpoints included number of genital ulcers (GU) at wk 12, efficacy over time (AUC for OU and and GU, first 12 wks), and AEs. Results: 111 patients (mean age 34.5±10.1 years, 69% women) were randomized (55 APR, 56 PBO) and 95 completed treatment phase (50 APR, 45 PBO). At wk 12, significantly more patients in APR group had a complete response in OU (71% [39/55], APR; 29% [16/56], PBO; p<0.0001). Mean (±SD) number of OU at wk 12 was 0.5±1.03 with APR and 2.1±2.58 with PBO (p<0.0001). Figure shows the mean number of OU over time. Beneficial effect of APR on OU continued in open phase but disappeared once drug was stopped at wk 24. Improvement in OU pain was significantly higher with APR (-44.7±24.30 vs -16.0±32.54; p<0.0001). In pts with GU at baseline, 10/10 in APR had no GU at wk12 vs 3/6 had no GU in PBO (p= 0.04). Serious AEs were 1 diplegia, transient and not thought to be related to APR, 1 anal fissure, and hemorrhoids with APR while 2 disease flares and 1 fever episode with PBO. Image/graph: Conclusions: APR was effective in the treatment of OU, the cardinal manifestation of BS, with an acceptable safety profile. There were also indications of efficacy in treating GU, a highly specific lesion for BS. Further trials are warranted to test the efficacy of APR for other manifestations of BS. Disclosure of Interest : G. Hatemi: None Declared, M. Melikoglu: None Declared, R. Tunc: None Declared, C. Korkmaz: None Declared, B. Ozturk: None Declared, C. Mat Paid instructor for: Celgene, P. Merkel Grant/research support from: Celgene, K. Calamia: None Declared, Z. Liu Employee of: Celgene, L. Pineda Employee of: Celgene, R. Stevens Shareholder of: Celgene, Employee of: Celgene, H. Yazici: None Declared, Y. Yazici Grant/research support from: Celgene, Consultant for: Celgene